Psychological disturbances, autonomous heart rate regulation, and sudden death risk in myocardial infarction patients - S. A. Boldueva; O. V. Trofimova; A. A. Gimgina (Российский кардиологический журнал, 2008)
Clinical and psychological examination was performed in 320 patients, 18–20 days after diagnosing acute myocardial infarction (AMI). In 56 %, anxiety and depressive symptoms were observed. These patients, comparing to those without psychological disturbances, demonstrated greater manifestation of autonomic dysbalance during heart rate variability (HRV) assessment (increased sympathetic and deceased vagal activity). Disturbed HRV correlated with progressing anxiety and depression. In sudden death group, psychological and HRV disturbances were substantially more manifested, regardless of AMI clinical course severity. This could trigger fatal arrhythmia development. In participants with anxiety and depression symptoms, including those with sudden death, personality anxiety level was higher.